Religion and the State in Turkish Universities - Seggie, F. author. aut Link
XXII, 207 p.
Keywords: This book explores educational and cultural experiences of 'part-time' unveilers during their undergraduate degree programs in public institutions in Turkey. The term 'part-time unveiler' refers to undergraduate female students who cover their hair in their private lives but who remove the headscarf while at a Turkish university.